2006
DOI: 10.1007/s11095-006-9462-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of a QSAR Model for Binding of Tripeptides and Tripeptidomimetics to the Human Intestinal Di-/Tripeptide Transporter hPEPT1

Abstract: Structural information on tripeptide properties influencing the binding to hPEPT1 was extracted from the QSAR model. This information may contribute to the drug design process of tripeptides and tripeptidomimetics where hPEPT1 is targeted as an absorptive transporter for improvement of intestinal absorption. To our knowledge, this is the first time a correlation between VolSurf descriptors and binding affinities for hPEPT1 has been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…Comparing the present model with the QSAR model developed by Andersen et al employing VolSurf descriptors and with the VolSurf part of the model created by Larsen et al, the overall picture is similar (16,17). Binding is a prerequisite for transport which the resemblance between the affinity and translocation models support.…”
Section: Modelling Of Structure-translocation Relationship Of Tripeptsupporting
confidence: 63%
See 2 more Smart Citations
“…Comparing the present model with the QSAR model developed by Andersen et al employing VolSurf descriptors and with the VolSurf part of the model created by Larsen et al, the overall picture is similar (16,17). Binding is a prerequisite for transport which the resemblance between the affinity and translocation models support.…”
Section: Modelling Of Structure-translocation Relationship Of Tripeptsupporting
confidence: 63%
“…With the aid of VolSurf descriptors, it has been possible to model the relationship between binding and structure of hPEPT1 ligands (16,17). The present study is the first evidence for the VolSurf descriptors being descriptive of the more complicated process of translocation via hPEPT1.…”
Section: Modelling Of Structure-translocation Relationship Of Tripeptmentioning
confidence: 66%
See 1 more Smart Citation
“…A previous study has shown the value of VolSurf descriptors to identify and rate structural features in tripeptides that are significant for their affinity to hPEPT1. [15] The VolSurf model takes into account descriptors, like molecular size and hydrophilic and hydrophobic properties, by applying GRID 3D molecular interaction fields (MIFs), and energy calculations of the interaction energy between the ligand and different probes. VolSurf descriptors for the 14, Nterminal amino acid substituted tripeptides shown in Table 1 were superimposed on the data set representing all possible 8000 proteinogenic tripeptides using the probes H 2 O, DRY, and O ( Figure 1).…”
Section: Structural Design Strategymentioning
confidence: 99%
“…[15] Increase in the first principal component mainly reflects a decrease in the polarity of the peptide. Decrease in the second principal component predominantly reflects an increase in molecular weight.…”
Section: Structural Design Strategymentioning
confidence: 99%